ANXIETY OF BETTINA DANIELS IN DANIELLE STEEL’S NOVEL LOVING (1980): A PSYCHOANALYTIC APPROACH - UTAMI, GLASSINEA NURUL (2010)

(untitled)
The object of the research is the novel entitled Loving by Danielle Steel. The study gives focus on anxiety of Bettina Daniels in Danielle Steel’s Loving. The aims of the study are: 1) To analyze the novel based on the structural elements of the novel, 2) To analyze the anxiety of the major character based on the psychoanalytic perspective.